'I bend, indeed, but never break': Formal rules and informal processes of candidate selection for European elections. (January 2020) - Kelbel, Camille
Many of the criticisms commonly made of modern political parties concern their alleged lack of transparency and use of informality in their inner organization. Yet, little is known about the extent to which parties really bend their rules. This article investigates whether and how political parties use informality in one central aspect of intra-party life: candidate selection. More specifically, selection procedures for European elections are examined since party actions at the European level are still under little scrutiny from the media and the voters, hence granting them much leeway. To compare rules with practices, actors and levels cited in 51 party statutes are matched with their uses in 2014, gathered through a survey and interviews of Members of the European Parliament (MEPs). Even though informal processes are found to be generally less inclusive than the rules prescribed, divergences are often modest, suggesting that parties do not necessarily rely on informality in their day-to-day functioning.